2020
DOI: 10.3390/ijms21197137
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity Evaluation of Indium Phosphide Quantum Dots with Different Surface Modifications in BALB/c Mice

Abstract: InP QDs have shown a great potential as cadmium-free QDs alternatives in biomedical applications. It is essential to understand the biological fate and toxicity of InP QDs. In this study, we investigated the in vivo renal toxicity of InP/ZnS QDs terminated with different functional groups—hydroxyl (hQDs), amino (aQDs) and carboxyl (cQDs). After a single intravenous injection into BALB/c mice, blood biochemistry, QDs distribution, histopathology, inflammatory response, oxidative stress and apoptosis genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Exposure to high concentrations by intravenous injection into mice was found to cause death and acute inflammation as well as alterations in hematological and biochemical parameters, and the CQD‐modified QDs produced more pronounced toxic effects than the other two, while no significant toxic effects were observed at lower concentrations. Similar findings can be demonstrated in the and investigations of Li, Chen, Yang et al (2020) and Lin et al (2020).…”
Section: Factors Influencing Bbb Permeabilitysupporting
confidence: 91%
“…Exposure to high concentrations by intravenous injection into mice was found to cause death and acute inflammation as well as alterations in hematological and biochemical parameters, and the CQD‐modified QDs produced more pronounced toxic effects than the other two, while no significant toxic effects were observed at lower concentrations. Similar findings can be demonstrated in the and investigations of Li, Chen, Yang et al (2020) and Lin et al (2020).…”
Section: Factors Influencing Bbb Permeabilitysupporting
confidence: 91%
“…Mouse body weight, organ weight, and histology of kidney and liver tissues showed no differences compared to mice receiving PBS control injections (Figure and Table ). The kidney and liver were of heightened interest in this study; studies have shown that InP QDs have a propensity to pass through or accumulate in these organs. , Albumin, a serum parameter indicative of hepatic and renal health, was comparable to control for all treatment groups (Figure C). The InP QDs also did not cause any inflammation in the mice, as shown by the serum levels of TNF-α and IL-6 (Figure A,B), markers for general inflammation and immune response, and consistent spleen weight across groups (Figure C).…”
Section: Discussionmentioning
confidence: 89%
“…The material comprising a QD therapy may also contribute to toxicity. However, indium phosphide is traditionally not considered to be toxic unless at very high concentrations. , When compared to cadmium telluride (CdTe), a material that has been well studied for QD applications, , InP is considered much more biologically compatible. ,,, Considering that our QD treatment shows in vitro efficacy at less than 5 μM concentration, there is unlikely to be enough indium present to cause adverse effects in the host. Indium phosphide QDs were shown to accumulate in liver and spleen of rats in a study by Yaghini et al, but toxicity as a result of this accumulation was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, ROS produced during oxidative metabolism in organisms and eliminated by antioxidant defense systems maintain homeostasis 48 , 49 . Excessive ROS production and insufficient antioxidant responses can lead to oxidative stress 50 , 51 .…”
Section: Resultsmentioning
confidence: 99%